High-temperature-resistant lipophilic nano-micron silicon dioxide blocking dispersion system as well as preparation method and application thereof
Through the development of anti -high -temperature littering nano -micronicular silicon blocking and decentralization system, the problem of insufficient performance of oil -based drilling liquid micro -cracks was solved, and effective sealing and stability of the well wall of the well wall were improved under high temperature conditions.
Patent Information
- Application Number
- CN202310894527.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-20
- Publication Date
- 2025-01-21
AI Technical Summary
The micro-crack sealing performance of existing oil-based drilling fluids is insufficient, especially under high temperature conditions, which leads to instability of the formation well wall.
Develop a high-temperature lipophilic nano- and micron silica blocking dispersion system. Through the combination of hydrophobically modified nano- and micron-sized silica, dispersant and dispersion medium, a blocking agent with a wide particle size distribution range is formed. , can effectively seal micro-cracks of different nanometer and micron scales.
The blocking and dispersing system can still be effectively blocked after the aging of 220 ° C. The high temperature and high pressure filtration loss of the oil -based diamond fluorescent fluid under 1 % increase conditions have significantly reduced the amount of filtering of the PPA sand disc, and the stability of the well wall has increased.
Smart Images

Figure BDA0004349209570000091 
Figure BDA0004349209570000101 
Figure BDA0004349209570000111
Abstract
Description
Technical Field
[0001] The present application relates to a high-temperature resistant oleophilic nano-micron silica plugging dispersion system and a preparation method and application thereof, belonging to the technical field of unconventional oil and gas field drilling. Background Art
[0002] CN202110708470.3 discloses a high temperature resistant modified nano-silica plugging agent. The product is synthesized step by step by enamine compounds, diallyl compounds, long-chain alkyl lipid compounds containing olefinic bonds, amino-containing silane coupling agents, and cross-linking agent divinylbenzene modified nano-silica, and successfully prepares a modified nano-silica plugging agent that can resist high temperatures of 160°C. The particle size is between 78-300nm, and the plugging performance is significantly improved compared to similar plugging agents. However, its temperature resistance needs to be further improved, and the particle size distribution range needs to be widened in order to achieve effective plugging of microcracks at different nanometer scales.
[0003] CN202210530727.5 discloses an oil-based drilling fluid system based on hydrophobic nano-silica and a preparation method thereof. The oil-based drilling fluid system mainly includes hydrophobically modified nano-silica, octadecyl trimethyl ammonium chloride, organic soil, oxidized asphalt, calcium oxide, barite, white oil and water. The raw materials are widely available, the upper temperature limit is 220°C, the plugging and inhibition are strong, and it has good reservoir protection ability. However, it is difficult to directly add solid nanomaterials to the drilling fluid during the on-site preparation process, and the nano-silica particle size distribution is less than 30nm, which is not conducive to fully plugging different nano-micrometer scale microcracks. Summary of the invention
[0004] As my country's unconventional oil and gas production continues to increase, the difficulty of drilling is also increasing. Oil-based drilling fluid plays an increasingly important role in unconventional oil and gas exploration and development due to its better inhibition and lubricity than water-based drilling fluid. When oil-based drilling fluid enters the formation through microcracks, liquid invasion and pressure transmission will cause the formation wellbore instability. Therefore, improving the microcrack plugging ability of oil-based drilling fluid is a key way to solve the problem of wellbore instability of oil-based drilling fluid. At present, the research on plugging agents for oil-based drilling fluid in China started late, there are few products, and the plugging performance needs to be improved. The commonly used plugging agents for high-temperature oil-based drilling fluids are asphalt, super calcium, resin and other materials. There are few means to effectively plug microcracks in the formation at the nano-micrometer scale. It is urgent to develop nano-micrometer plugging agents for high-temperature resistant oil-based drilling fluids. Organic plugging agents are easily degraded under high temperature conditions, while nano-silica has good high temperature resistance and can be well dispersed in oil-based drilling fluids through hydrophobic modification. In addition, nano-silicon dioxide has good strength, simple preparation method and low price, and can be used as nano-micro plugging agent for oil-based drilling fluid through modification and particle size grading.
[0005] According to the first aspect of the present application, a high temperature resistant lipophilic nano-micron silica plugging dispersion system is provided. The particle size distribution range of the high temperature resistant lipophilic nano-micron silica plugging dispersion system spans a wide range of 5nm-30μm, which is conducive to fully plugging microcracks of different nano-micron scales.
[0006] A high temperature resistant lipophilic nano-micron silica plugging dispersion system, comprising hydrophobically modified nano-scale silica, hydrophobically modified micro-scale silica, a dispersant, and a dispersion medium;
[0007] The dispersant is selected from at least one of alkyl sulfonates, alkyl polyoxyethylene ethers, and alkyl amidopropyl betaine;
[0008] The dispersion medium is white oil;
[0009] The particle size distribution of the nano-micron silica plugging dispersion system is D10 of 25-40nm, D50 of 235-275nm, and D90 of 1200-1500nm;
[0010] The particle size distribution of the nano-micron silicon dioxide plugging dispersion system is 5nm-30μm.
[0011] Optionally, the particle size of the nano-micron silica plugging dispersion system is independently selected from 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 15nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 120nm, 140nm, 150nm, 160nm, 180nm, 200nm, 220nm, 230nm, 240nm, 242nm, 248nm, 250nm, 255nm, 260nm, 265nm, 269nm, 280nm, 300nm, 350nm, 400nm, Any value among 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm, 25μm, 26μm, 27μm, 28μm, 29μm, 30μm, or any range between any two of them.
[0012] Optionally, D10 of the nano-micron silica plugging dispersion system is independently selected from any value among 25nm, 26nm, 27nm, 28nm, 29nm, 30nm, 31nm, 32nm, 33nm, 34nm, 35nm, 36nm, 37nm, 38nm, 39nm, 40nm or any range value between two of them.
[0013] Optionally, D50 of the nano-micron silica plugging dispersion system is independently selected from any value among 235 nm, 240 nm, 242 nm, 248 nm, 250 nm, 255 nm, 260 nm, 265 nm, 269 nm, 275 nm, or a range value between any two of them.
[0014] Optionally, D90 of the nano-micron silica plugging dispersion system is independently selected from any value among 1200nm, 1230nm, 1233nm, 1300nm, 1327nm, 1397nm, 1442nm, 1500nm or a range value between any two thereof.
[0015] Preferably, the particle size distribution of the nano-micron silica plugging dispersion system is D10 of 29-36 nm, D50 of 242-269 nm, and D90 of 1233-1442 nm.
[0016] As a specific implementation of the present application, the dispersion medium is selected from at least one of white oil No. 3, white oil No. 5, and white oil No. 7.
[0017] As a specific implementation of the present application, the content of the dispersant is 1%-4% of the content of the hydrophobically modified nano-silicon dioxide.
[0018] As a specific implementation of the present application, the content of the dispersant is 1.5%-2.5% of the content of the hydrophobically modified nano-silicon dioxide.
[0019] Optionally, the content ratio of the dispersant to the hydrophobically modified nano-silica is independently selected from any value of 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, or any range between the two.
[0020] As a specific implementation of the present application, the solubility of the nano-micron silica plugging dispersion system is 40%-45%.
[0021] As a specific implementation of the present application, in the nano-micron silica plugging dispersion system, the effective solid content is greater than 40%.
[0022] According to the second aspect of the present application, a method for preparing a high temperature resistant lipophilic nano-micron silica plugging dispersion system is provided. The preparation process is simple, the raw materials are cheap, the system is environmentally friendly and non-toxic, and the system is easy to commercialize.
[0023] A method for preparing a high temperature resistant lipophilic nano-micron silica plugging dispersion system comprises the following steps:
[0024] S1, obtaining hydrophobically modified nano-scale silica and hydrophobically modified micro-scale silica;
[0025] S2, mixing materials containing a dispersant and a dispersion medium I to obtain a dispersed liquid phase;
[0026] S3, adding hydrophobically modified nano-scale silicon dioxide with median particle sizes of 20-40 nm, 80-150 nm, and 500-600 nm to the dispersion phase in sequence for mixing II to obtain a nano-dispersion liquid;
[0027] S4. Add hydrophobically modified micron-sized silica with median particle sizes of 2-5 μm and 6-10 μm respectively into the nano-dispersion liquid in sequence for mixing III to obtain the nano-micron silica plugging dispersion system.
[0028] As a specific implementation of the present application, step S1 includes the following steps:
[0029] S1.1, respectively, adding nano-scale silicon dioxide or micro-scale silicon dioxide to a toluene solution, heating to 40-90°C, preferably 55-65°C; introducing nitrogen after heating for 10-60 minutes, preferably 20-30 minutes; then continuing to heat to 80-100°C, preferably 85-95°C;
[0030] S1.2, adding a hydrophobic modifier to the solution obtained in step S1.1 for modification for 3-6 hours, preferably 4-5 hours, and obtaining the corresponding hydrophobically modified nano-scale silica / hydrophobically modified micro-scale silica through distillation, washing, filtering and vacuum drying.
[0031] As a specific implementation of the present application, the hydrophobic modifier may be a silane coupling agent.
[0032] The silane coupling agent is selected from at least one of 3-aminopropyltrimethoxysilane (KH540), 3-aminopropyltriethoxysilane (KH550), and γ-methacryloxypropyltrimethoxysilane (KH570).
[0033] As a specific implementation of the present application, in step S2, the conditions of mixing I are as follows:
[0034] Temperature is 25-35℃;
[0035] Stirring speed 100-200r / min;
[0036] The stirring time is 10-20 minutes.
[0037] As a specific embodiment of the present invention, in step S3, the conditions of mixing II are as follows:
[0038] Temperature is 25-35℃;
[0039] Stirring speed 200-300r / min;
[0040] The stirring time is 20-30 minutes.
[0041] As a specific implementation of the present application, in step S4, the conditions for mixing III are as follows:
[0042] Temperature is 25-35℃;
[0043] Stirring speed 300-400r / min;
[0044] The stirring time is 30-40 minutes.
[0045] As a specific embodiment of the present application, in step S3, the mass ratio of the hydrophobically modified nano-silica with a median particle size of 20-40 nm, the hydrophobically modified nano-silica with a median particle size of 80-150 nm, and the hydrophobically modified nano-silica with a median particle size of 500-600 nm is 1:0.5-1.5:0.5-1.5.
[0046] As a specific embodiment of the present application, the mass ratio of the hydrophobically modified nano-silica with a median particle size of 20-40nm, the hydrophobically modified nano-silica with a median particle size of 80-150nm, and the hydrophobically modified nano-silica with a median particle size of 500-600nm is 1:0.8-1.2:0.8-1.2.
[0047] Optionally, the mass ratio of the hydrophobically modified nano-scale silica with a median particle size of 20-40 nm, the hydrophobically modified nano-scale silica with a median particle size of 80-150 nm, and the hydrophobically modified nano-scale silica with a median particle size of 500-600 nm is 1:1:1.
[0048] As a specific implementation of the present application, in step S4, the mass ratio of the hydrophobically modified micron-sized silica with a median particle size of 2-5 μm to the hydrophobically modified micron-sized silica with a median particle size of 6-10 μm is 1:0.5-1.5.
[0049] Optionally, in step S4, the mass ratio of the hydrophobically modified micron-sized silica with a median particle size of 2-5 μm to the hydrophobically modified micron-sized silica with a median particle size of 6-10 μm is independently selected from any value of 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5 or any range value between two of them.
[0050] As a specific implementation of the present application, the mass ratio of the total hydrophobically modified micron-sized silica added in step S4 to the total hydrophobically modified nano-sized silica added in step S3 is 1:0.5-1.5.
[0051] Optionally, the mass ratio of the total hydrophobically modified micron-sized silica added in step S4 to the total hydrophobically modified nano-sized silica added in step S3 is independently selected from any value among 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5 or any range value between two of them.
[0052] According to the third aspect of the present application, a high temperature resistant lipophilic nano-micron silica plugging dispersion system is provided for use in oil-based drilling fluid. The high temperature resistant lipophilic nano-micron silica plugging dispersion system has good temperature resistance and can still achieve effective plugging after aging at 220°C. Under the condition of 1% addition, the high temperature and high pressure filtration loss reduction rate of oil-based drilling fluid is greater than 30%, and the filtration loss reduction rate of oil-based drilling fluid PPA sand disk is greater than 30%. And it has good compatibility with oil-based drilling fluid. Under the condition of 1% addition, the viscosity of oil-based drilling fluid is slightly increased, the filtration loss is effectively reduced, and the demulsification voltage is increased.
[0053] Application of the nano-micron silica plugging dispersion system or the nano-micron silica plugging dispersion system obtained by the above-mentioned preparation method in oil-based drilling fluid.
[0054] As a specific embodiment of the present invention, when the amount of the nano-micron silica plugging dispersion system is 1%, the high-temperature and high-pressure filtration loss reduction rate of the oil-based drilling fluid is greater than 30%;
[0055] The PPA sand plate filtration loss reduction rate of oil-based drilling fluid is >30%.
[0056] The beneficial effects of this application include:
[0057] 1) The present application provides a high temperature resistant and lipophilic nano-micron silica plugging dispersion system, which has a wide particle size distribution range of 5nm-30μm, which is conducive to fully plugging microcracks of different nano-micron scales; the plugging dispersion system has good temperature resistance and can still achieve effective plugging after aging at 220℃. Under the condition of 1% addition, the high temperature and high pressure filtration loss reduction rate of oil-based drilling fluid is greater than 30%, and the filtration loss reduction rate of oil-based drilling fluid PPA sand disk is greater than 30%; the effective solid content of the plugging dispersion system is greater than 40%, and it has good compatibility with oil-based drilling fluid. Under the condition of 1% addition, the viscosity of the oil-based drilling fluid is slightly increased, the filtration loss is effectively reduced, and the demulsification voltage is increased.
[0058] 2) The present application provides a method for preparing a high-temperature resistant and lipophilic nano-micron silica plugging dispersion system, which has a simple preparation process, cheap raw materials, is environmentally friendly and non-toxic, and is easy to commercialize. DETAILED DESCRIPTION
[0059] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0060] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels, including:
[0061] The dispersant was selected from Texas Continental Shelf Petroleum Engineering Technology Co., Ltd.
[0062] Unless otherwise specified, conventional test methods or test methods recommended by the instrument shall be used.
[0063] Example 1
[0064] (1) Add 5 g of nano-scale and 5 g of micro-scale silica to 50 ml of toluene solution, heat to 60° C., introduce nitrogen for 25 min, continue to heat to 90° C., add 0.5 g of 3-aminopropyltrimethoxysilane (KH540), react for 4.5 h, distill, wash, filter, and vacuum dry to obtain a modified product;
[0065] (2) adding 0.2 g of sodium pentadecylsulfonate to 50 ml of white oil No. 3 for a first mixing (stirring speed of 150 r / min, temperature of 30° C., time of 15 min), the amount of dispersant added being 2% of the amount of silicon dioxide added, to obtain a dispersed liquid phase;
[0066] (3) adding 5 g, 5 g, and 5 g of the modified nano-silicon dioxide with a median particle size of 30 nm, 100 nm, and 500 nm, respectively, obtained in step (1) to the dispersed liquid phase for a second mixing (stirring speed of 250 r / min, temperature of 30° C., and time of 25 min) to obtain a nano-dispersion liquid;
[0067] (4) The modified micronized silica with a median particle size of 3 μm and 8 μm, 7.5 g and 7.5 g respectively, obtained in step (1) were added to the nano-dispersed liquid phase for a third mixing (stirring speed of 350 r / min, temperature of 30° C., time of 35 min) to obtain a nano-micro composite dispersion.
[0068] The particle size and solubility results of Example 1 are shown in Table 1.
[0069] Example 2
[0070] (1) Add 5 g of nano-scale and 5 g of micro-scale silica to 50 ml of toluene solution, heat to 60° C., introduce nitrogen for 30 min, continue to heat to 90° C., add 1 g of 3-aminopropyltriethoxysilane (KH550), react for 5 h, distill, wash, filter, and vacuum dry to obtain a modified product;
[0071] (2) adding 0.2 g of sodium pentadecylsulfonate to 50 ml of white oil No. 3 for a first mixing (stirring speed of 150 r / min, temperature of 30° C., time of 15 min), the amount of dispersant added being 2% of the amount of silicon dioxide added, to obtain a dispersed liquid phase;
[0072] (3) adding 5 g, 5 g, and 5 g of the modified nano-silicon dioxide with a median particle size of 40 nm, 120 nm, and 550 nm, respectively, obtained in step (1) to the dispersed liquid phase for a second mixing (stirring speed of 250 r / min, temperature of 30° C., and time of 25 min) to obtain a nano-dispersion liquid;
[0073] (4) The modified micron silicon dioxide with a median particle size of 4 μm and 10 μm obtained in step (1), 7.5 g and 7.5 g respectively, was added to the nano-dispersed liquid phase for a third mixing (stirring speed of 350 r / min, temperature of 30° C., time of 35 min) to obtain a nano-micro composite dispersion.
[0074] The particle size and solubility results of Example 2 are shown in Table 1.
[0075] Example 3
[0076] (1) Add 5 g of nano-scale and 5 g of micro-scale silica to 50 ml of toluene solution, heat to 60° C., introduce nitrogen for 30 min, continue to heat to 90° C., add 0.7 g of γ-methacryloxypropyltrimethoxysilane (KH570), react for 5 h, distill, wash, filter, and vacuum dry to obtain a modified product;
[0077] (2) adding 0.2 g of sodium pentadecylsulfonate to 50 ml of white oil No. 3 for a first mixing (stirring speed of 150 r / min, temperature of 30° C., time of 15 min), the amount of dispersant added being 3% of the amount of silicon dioxide added, to obtain a dispersed liquid phase;
[0078] (3) adding 5 g, 5 g, and 5 g of the modified nano-silicon dioxide with a median particle size of 20 nm, 80 nm, and 500 nm, respectively, obtained in step (1) to the dispersed liquid phase for a second mixing (stirring speed of 250 r / min, temperature of 30° C., and time of 25 min) to obtain a nano-dispersion liquid;
[0079] (4) The modified micronized silica with a median particle size of 2 μm and 6 μm, 7.5 g and 7.5 g respectively, obtained in step (1) were added to the nano-dispersed liquid phase for a third mixing (stirring speed of 350 r / min, temperature of 30° C., time of 35 min) to obtain a nano-micro composite dispersion.
[0080] The particle size and solubility results of Example 3 are shown in Table 1.
[0081] Example 4
[0082] (1) Add 5 g of nano-scale and 5 g of micro-scale silica to 50 ml of toluene solution, heat to 60° C., introduce nitrogen for 30 min, continue to heat to 90° C., add 0.5 g of γ-methacryloxypropyltrimethoxysilane (KH570), react for 5 h, distill, wash, filter, and vacuum dry to obtain a modified product;
[0083] (2) adding 0.2 g of sodium pentadecylsulfonate to 50 ml of white oil No. 5 for a first mixing (stirring speed of 150 r / min, temperature of 30° C., time of 15 min), the amount of dispersant added being 3% of the amount of silicon dioxide added, to obtain a dispersed liquid phase;
[0084] (3) adding 5 g, 5 g, and 5 g of the modified nano-silicon dioxide with a median particle size of 25 nm, 140 nm, and 600 nm, respectively, obtained in step (1) to the dispersed liquid phase for a second mixing (stirring speed of 250 r / min, temperature of 30° C., and time of 25 min) to obtain a nano-dispersion liquid;
[0085] (4) 7.5 g and 7.5 g of modified micron silicon dioxide with a median particle size of 5 μm and 8 μm respectively obtained in step (1) were added to the nano-dispersion liquid phase for a third mixing (stirring speed of 350 r / min, temperature of 30° C., time of 35 min) to obtain a nano-micro composite dispersion.
[0086] The particle size and solubility results of Example 4 are shown in Table 1.
[0087] Comparative Example 1
[0088] The other steps are the same as those in Example 1, except that the median particle size of the modified nano-silica in step (3) is changed, that is, 5 g of 15 nm, 5 g of 70 nm, and 5 g of 400 nm of modified nano-silica are added in sequence to obtain a nano-micron composite dispersion.
[0089] Comparative Example 2
[0090] The other steps are the same as those in Example 1, except that the median particle size of the modified micron silica in step (4) is changed, that is, 7.5 g of 1 μm and 7.5 g of 4 μm modified micron silica are added in sequence to obtain a nano-micro composite dispersion.
[0091] Comparative Example 3
[0092] The other steps are the same as those in Example 1, except that the order of adding the modified micron silicon dioxide in step (3) is changed, that is, 5 g of modified nano silicon dioxide with a median particle size of 50 nm, 5 g of 170 nm, and 5 g of 700 nm are added in sequence to obtain a nano-micro composite dispersion.
[0093] Comparative Example 4
[0094] The other steps were the same as those in Example 1, except that the order of adding the modified micron silica in step (4) was changed, that is, 7.5 g of modified micron silica with a median particle size of 7 μm and 7.5 g of 12 μm were added in sequence to obtain a nano-micro composite dispersion.
[0095] The particle size and solubility results of the products of Examples 1-4 are shown in Table 1.
[0096] Table 1
[0097]
[0098]
[0099] Test Case
[0100] The performance of the high temperature resistant lipophilic nano-micron silica plugging dispersion system prepared in Example 1 was tested.
[0101] 1. Particle size distribution of nano-micron silica dispersion system
[0102] The high temperature resistant lipophilic nano-micron silica plugging dispersion system prepared by mixing five nano-micron silicas with different particle size distributions has a wide particle size distribution range of 5nm-30μm. Among them, taking Example 1 as an example, its D10 is 33nm, D50 is 248nm, and D90 is 1233nm. The nano-micron material with a wide particle size distribution range can achieve effective plugging of micro cracks of different nano-micron scales.
[0103] 2. Effect of nano-micron silica dispersion system on rheology and filtration properties of oil-based drilling fluids
[0104] The present invention mainly describes the application of nano-micron silicon dioxide dispersion system by the following high temperature resistant oil-based drilling fluid formula. The specific formula is: base oil (white oil No. 3) + primary emulsifier (SMEMUL-1) + secondary emulsifier (SMEMUL-2) + wetting agent (SMWET) + brine (25% calcium chloride solution) + organic soil (40W HT) + shear enhancer (SMHSFA-H) + fluid loss reducer (SMFLA-O) + alkali (calcium oxide) + plugging agent (super calcium) + weighting agent (barite).
[0105] The specific configuration process is as follows:
[0106] Measure 255mL of white oil No. 3 into a high-stirring cup, add 15g of primary emulsifier (SMEMUL-1), 9g of secondary emulsifier (SMEMUL-1) and 3g of wetting agent (SMWET), place in a high-speed stirrer and stir at 12000r / min for 15min; measure 45mL of calcium chloride solution and add it into the high-stirring cup, and continue stirring for 20min; weigh 12g of organic soil (60S HT), slowly add it into the high-stirring cup, and stir for 20min; continue to weigh 4g of shearing agent (SMHSFA-H), add it into the high-stirring cup, and stir for 20min; add 12g of filtrate reducer (SMFLA-O) into the high-stirring cup, and stir for 10min; add 12g of alkali (calcium oxide) into the high-stirring cup, and stir for 10min; then add 6g of plugging agent (super calcium) into the high-stirring cup, and stir for 10min; finally, add 270g of weighting agent (barite) and stir for 20min.
[0107] After being fully stirred, the formula is marked as drilling fluid-1. Taking Example 1 as an example, 1.5g, 3g, 6g and 9g of nano-micron silica plugging dispersion system are added to drilling fluid-1, respectively, and marked as drilling fluid-2, drilling fluid-3, drilling fluid-4 and drilling fluid-5, respectively.
[0108] According to the National Standard of the People's Republic of China GB / T16783.2-□2012 "Field Test of Drilling Fluids in Petroleum and Natural Gas Industry Part 2: Oil-based Drilling Fluids", the rheological properties, filtration loss and demulsification voltage of five oil-based drilling fluid formulations were tested after aging at 220°C. The experimental results are shown in Table 2.
[0109] Table 2
[0110]
[0111] Note: AV-apparent viscosity, unit: mPa·s; PV-plastic viscosity, unit: mPa·s; YP-dynamic shear force, unit: Pa; API-medium pressure filtration loss, unit: mL; HTHP-high temperature and high pressure filtration loss (180℃), unit: mL; ES demulsification voltage, unit: V.
[0112] As shown in Table 2, compared with the basic drilling fluid formula, the addition of nano-micron silica dispersion system can improve the viscosity and shear of the drilling fluid, and the dynamic-plastic ratio remains basically stable, which is beneficial to improving the rock carrying capacity; and can effectively reduce the medium-pressure filtration loss and high-temperature and high-pressure filtration loss. Under the condition of 1% addition, the medium-pressure filtration loss reduction rate is 37.5%, and the high-temperature and high-pressure filtration loss reduction rate is 42.1%. It has good filtration loss reduction performance and is beneficial to maintaining the stability of the formation wellbore; at the same time, with the gradual increase in the amount of nano-micron silica dispersion system, the demulsification voltage of the oil-based drilling fluid increases and the emulsification stability is enhanced.
[0113] 3. Effect of nano-micron silica dispersion system on plugging properties of oil-based drilling fluid
[0114] The PPA drilling fluid plugging performance evaluation experimental device was used to evaluate the sand plate filtration loss of 6 drilling fluids at 180°C after aging at 220°C. The experimental results are shown in Table 3. As shown in Table 3, the addition of nano-micron silica dispersion system can effectively reduce the sand plate filtration loss of drilling fluid. Under the condition of 1% addition, the PPA filtration loss was reduced from 7.2mL to 3.2mL, with a reduction rate of 55.6%, which shows that the high-temperature resistant lipophilic nano-micron silica plugging dispersion system has a good plugging agent and can prevent the intrusion of drilling fluid in the formation. When the particle size distribution is outside "D10 is 25-40nm, D50 is 235-275nm, and D90 is 1200-1500nm" (Comparative Example 1), the plugging performance is much lower than that of Formula 1-5.
[0115] Table 3
[0116]
[0117] The performance test was conducted on the nano-micron silica plugging dispersion system prepared in Comparative Examples 1-4. The test and formulation were the same as Formula 1 of Example 1. The plugging effect of Comparative Examples 1-4 was much weaker than that of Example 1-4.
[0118] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A high temperature resistant lipophilic nano-micron silica plugging dispersion system, characterized in that: It includes hydrophobically modified nano-sized silica, hydrophobically modified micron-sized silica, a dispersant, and a dispersion medium; The dispersant is selected from at least one of alkyl sulfonates, alkyl polyoxyethylene ethers, and alkyl amidopropyl betaine; The dispersion medium is white oil; The particle size distribution of the nano-micron silica plugging dispersion system is D10 of 25-40nm, D50 of 235-275nm, and D90 of 1200-1500nm; The particle size distribution of the nano-micron silicon dioxide plugging dispersion system is 5nm-30μm.
2. The nano-micron silicon dioxide plugging dispersion system according to claim 1, characterized in that: The dispersion medium is selected from at least one of white oil No. 3, white oil No. 5, and white oil No. 7; And / or, the particle size distribution of the nano-micron silica plugging dispersion system is D10 of 29-36nm, D50 of 242-269nm, and D90 of 1233-1442nm; and / or, the content of the dispersant is 1%-4% of the content of the hydrophobically modified nano-scale silica; Preferably, the content of the dispersant is 1.5%-2.5% of the content of the hydrophobically modified nano-silicon dioxide.
3. The nano-micron silica plugging dispersion system according to claim 1 or 2, characterized in that: The solubility of the nano-micron silica plugging dispersion system is 40%-45%; And / or, in the nano-micron silicon dioxide plugging dispersion system, the effective solid content is greater than 40%.
4. The method for preparing the nano-micron silicon dioxide plugging dispersion system according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, obtaining hydrophobically modified nano-scale silica and hydrophobically modified micro-scale silica; S2, mixing materials containing a dispersant and a dispersion medium I to obtain a dispersed liquid phase; S3, adding hydrophobically modified nano-scale silicon dioxide with median particle sizes of 20-40 nm, 80-150 nm, and 500-600 nm to the dispersion phase in sequence for mixing II to obtain a nano-dispersion liquid; S4. Add hydrophobically modified micron-sized silica with median particle sizes of 2-5 μm and 6-10 μm respectively into the nano-dispersion liquid in sequence for mixing III to obtain the nano-micron silica plugging dispersion system.
5. The preparation method according to claim 4, characterized in that: Step S1 includes the following steps: S1.1, respectively add nano-scale silicon dioxide or micro-scale silicon dioxide to a toluene solution, heat it to 40-90°C, introduce nitrogen for 10-60 minutes after heating, and then continue to heat it to 80-100°C; S1.2, adding a hydrophobic modifier to the solution obtained in step S1.1 for modification for 3-6 hours, and obtaining the corresponding hydrophobically modified nano-scale silica or hydrophobically modified micro-scale silica through distillation, washing, filtering and vacuum drying.
6. The preparation method according to claim 4, characterized in that: In step S2, the conditions of mixing I are as follows: Temperature is 25-35℃; Stirring speed 100-200r / min; The stirring time is 10-20 minutes.
7. The preparation method according to claim 4, characterized in that: In step S3, the conditions of mixing II are as follows: Temperature is 25-35℃; Stirring speed 200-300r / min; The stirring time is 20-30min; And / or, in step S3, the mass ratio of the hydrophobically modified nano-silica with a median particle size of 20-40 nm, the hydrophobically modified nano-silica with a median particle size of 80-150 nm, and the hydrophobically modified nano-silica with a median particle size of 500-600 nm is 1:0.5-1.5:0.5-1.
5.
8. The preparation method according to claim 4, characterized in that: In step S4, the conditions for mixing III are as follows: Temperature is 25-35℃; Stirring speed 300-400r / min; The stirring time is 30-40 minutes; And / or, in step S4, the mass ratio of the hydrophobically modified micron-sized silica having a median particle size of 2-5 μm to the hydrophobically modified micron-sized silica having a median particle size of 6-10 μm is 1:0.5-1.5; And / or, the mass ratio of the total hydrophobically modified micron-sized silica added in step S4 to the total hydrophobically modified nano-sized silica added in step S3 is 1:0.5-1.
5.
9. Use of the nano-micron silica plugging dispersion system according to any one of claims 1 to 3 or the nano-micron silica plugging dispersion system obtained by the preparation method according to any one of claims 4 to 8 in oil-based drilling fluid.
10. The use according to claim 9, characterized in that: When the amount of the nano-micron silica plugging dispersion system added is 1%, the high-temperature and high-pressure filtration loss reduction rate of the oil-based drilling fluid is greater than 30%; The PPA sand plate filtration loss reduction rate of oil-based drilling fluid is >30%.
Citation Information
Patent Citations
High-temperature-resistant modified nano silicon dioxide blocking agent and oil-based drilling fluid
CN113355069A
Oil-based drilling fluid system based on hydrophobic nano silicon dioxide and preparation method of oil-based drilling fluid system
CN115074096A